Development of A Web-Based Application Measuring Student and Lecturer Satisfaction for Educational Service - Ayu Tri Wardani Wardani; Alifya NFH (Program Studi Teknik Komputer, 2025)
The development of student and lecturer satisfaction survey applications for web-based education services aims to improve the efficiency of feedback data collection and support data-based decision making. This research uses Extreme Programming (XP) method which involves planning, designing, coding, and testing stages. In the planning stage, user needs are identified to ensure the designed features are in line with the application's objectives. Designing is done using the Class Responsibility Collaborator (CRC) Cards approach to ensure the system design is structured and easy to develop. The coding stage uses PHP and MySQL to produce applications that meet the functional needs of the system, while the testing stage is carried out using the blackbox testing method to ensure each module works according to specifications. The results show that this application is able to improve the efficiency of the survey process, provide an easily accessible web-based platform, and produce structured survey data. The implementation of this application is expected to contribute to improving the quality of education services through valid and real-time survey data analysis. Keywords: Satisfaction Survey, Extreme Programming, PHP, MySQL, Blackbox Testing.